Sorghum Crackers (Sorghum bicolor L.) as an Effort in Utilizing Food Material of Local Wisdom in Lamongan City - Irvan Adhin Cholilie; Anni Rahmat; Azmi Alvian Gabriel; Yunita Siti Mardhiyyah; Yulia Nur Rohmawati; Ahmad Musonnif Dzulfikri; Eka Nur Fadilah; Anisah Firdausiah Oktarilivyana; Hans Febrianto Setyo (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
In an effort to meet the growing needs for food, feed and industrial materials, as well as to increase the income of farmers in dry climates, sorghum development is one of the alternatives that can be selected. This research uses sorghum to become three types of food processing, namely crackers, popped and sorghum sugar. However, at this stage only crackers are processed. The research was conducted in several stages, namely (i) making crackers, (ii) chemical analysis of crackers and (iii) organoleptic crackers testing. The independent variable which is the subject of the study is the type of shorgum used. This study used three types of sorghum, namely KD4, Kawali, and Samurai. From the results of the tests carried out for the sorghum crackers sample, it was found that this product could still be said to be balanced, even though the amount of energy from the fat was at the maximum threshold, namely in the range of 29-31%. Products with this category are not recommended for someone who is on a fat diet. As a snack category, this product can be good declared. Based on the organoleptic (sensory) test results also indicate that the product can be accepted by consumers.